Both reduced ovarian reserve and severe semen alterations are overrepresented in couples seeking assisted reproductive technology treatment for the first time: a cross-sectional study - Juan J. Tarín; Eva Pascual; Miguel A. García-Pérez; Aitana Monllor-Tormos; Antonio Cano (BMC, 2023)
Abstract Background Once a mate choice decision has been made, couples that fail to reach a live birth in natural and/or intrauterine insemination (IUI) cycles will likely visit fertility clinics seeking assisted reproductive technology (ART) treatment. During the more or less prolonged period of infertility experienced, those couples with mild/moderate reproductive anomalies would have advantage over couples displaying more severe reproductive alterations in achieving a natural or IUI conception. Thus, we can expect to find a progressive increase in the proportion of couples with more severe reproductive anomalies as duration of infertility rises. In this study, we aim to ascertain whether there is an association between male and female infertility diagnoses and duration of infertility in couples seeking ART treatment for the first time. Methods A cross-sectional analysis of 1383 infertile couples that sought ART treatment for the first time. Forward-stepwise binary logistic regression analyses were applied to calculate exponentiated regression coefficients. Results Men suffering from any combination of oligo-, astheno-, and teratozoospermia (ACOAT) exhibited higher odds of having a duration of infertility > 2 years compared with non-ACOAT men [odds ratio (95% confidence interval): 1.340 (1.030-1.744)]. Women from ACOAT couples displaying a duration of infertility > 2 years presented shorter menstrual cycles (P ≤ 0.047) and lower antral follicular count (AFC) values (P ≤ 0.008) and serum anti-Müllerian hormone (AMH) levels (P ≤ 0.007) than women from non-ACOAT couples exhibiting > 2 years of infertility. Likewise, AFC values (P ≤ 0.013) and serum AMH levels (P ≤ 0.001) were decreased when compared with women from ACOAT couples displaying ≤ 2 years of infertility. A relative low but significant percentage of ACOAT couples displaying > 2 years of infertility stood out for their smoking habits. Conclusions Couples consisting of ACOAT men and women with a relative low ovarian reserve are overrepresented in couples seeking ART treatment for the first time after experiencing > 2 years of infertility. This outcome leads us to develop a general hypothesis proposing that the origin of couple's infertility is a consequence of a process of positive assortative mating shaped by sexual selection forces.